Intellectual Property in the Global Trading System EU-China Perspective - Shi, Wei (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Having explored multifaceted issues of IPR enforcement, this book argues that IPR enforcement problem is not an actual outcome of Confucian philosophy and "to steal a book" is not an "elegant offence." This book demonstrates that counterfeiting and piracy are common inevitable consequences of inadequate economic development and a by-product of a unique set of socioeconomic crises deriving from the development of a dysfunctional institutional regime. By examining areas of compatibilities between European and Chinese cultures and analysing painful lessons from the US-China negotiations over IPR protection, this book uses the prism of EU-China trade relations to suggest ways to reconcile the minimum standards of TRIPs Agreement and the specific conditions of particular states, and provide insight into the unresolved issues as to how and when China's WTO commitments will be implemented.